Radiologist's Guide to Diagnosis of Fetal Cardiac Anomalies on Prenatal Ultrasound Imaging. Issue 1 (March 2019) - Revels, Jonathan Wesley; Wang, Sherry S.; Itani, Malak; Nasrullah, Ayesha; Katz, Douglas; Dubinsky, Theodore J.; Moshiri, Mariam
Abstract : Abstract: Congenital cardiac anomalies are a common finding during prenatal anatomical survey ultrasound examination. Cardiac anomalies are a major cause of prenatal and neonatal mortality and morbidity. If the anomaly is not lethal, most would require surgical correction. Therefore, early recognition of these abnormalities is essential for parental counseling and delivery planning, as well as analysis of neonatal treatment options. Although prenatal ultrasound plays an important role in identification of such anomalies, diagnosis and interpretation of imaging findings require familiarity and knowledge of the common imaging features. In this article, we provide a comprehensive review of ultrasound appearance of common fetal cardiac anomalies. Abstract : Supplemental digital content is available in the text.